2022
DOI: 10.3389/fpubh.2022.906106
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Drivers of Ghanaian Citizens' Adoption Intentions of Mobile Health Services

Abstract: Mobile health (m-health) application development and diffusion in developing countries have always been a challenge; therefore, research that seeks to provide an elucidation of the drivers of m-Health adoption is vital. Mobile health information systems and applications can contribute to the delivery of a good healthcare system. This study examined the factors influencing citizens' adoption of mobile health services. The Technology Acceptance Model (TAM) was used as the research underpinning for this study, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 117 publications
1
25
0
Order By: Relevance
“…Finally, the results for all samples showed that perceived ease of use was affected by mobile self-efficacy. Recent studies by Mensah (2022) and Song et al (2022) also concluded that mobile self-efficacy has a significant effect on perceived ease of use. This finding suggests that when pre-service and in-service teachers possess experience and self-efficacy in their use of applications on mobile devices, they will perceive the use of MAR to be easier.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, the results for all samples showed that perceived ease of use was affected by mobile self-efficacy. Recent studies by Mensah (2022) and Song et al (2022) also concluded that mobile self-efficacy has a significant effect on perceived ease of use. This finding suggests that when pre-service and in-service teachers possess experience and self-efficacy in their use of applications on mobile devices, they will perceive the use of MAR to be easier.…”
Section: Discussionmentioning
confidence: 97%
“…They studied the acceptance of mobile-based assessments among 145 senior high school students and found mobile self-efficacy was positively associated with perceived ease of use. Recently, Mensah (2022) found that this component positively affected the perceived ease of use of m-health services. Similar findings were found by Song et al (2022) on the factors that influence older adults' adoption of voice-user interface.…”
Section: Hypothesis 6bmentioning
confidence: 99%
“…Younger individuals with higher educational levels and greater digital competence are more likely to embrace these technologies (Tao et al ., 2023). Additionally, individual health beliefs and attitudes are significant predictors of adoption (Oloveze et al ., 2022) (Mensah, 2022). Perceived usefulness, perceived ease of use, and the perceived impact of the app on one’s health outcomes can drive initial adoption and sustained engagement (Mensah, 2022) (Wu et al ., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, individual health beliefs and attitudes are significant predictors of adoption (Oloveze et al ., 2022) (Mensah, 2022). Perceived usefulness, perceived ease of use, and the perceived impact of the app on one’s health outcomes can drive initial adoption and sustained engagement (Mensah, 2022) (Wu et al ., 2022). On the contrast, barriers such as privacy concerns, data security, and the fear of technology replacing human interactions can hinder adoption and lead to discontinuity (Jacob et al ., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The platform provides value to each of these user groups by enabling them to interact and exchange value with each other (Ardolino et al, 2020;Bakshi & Tandon, 2022;Mensah, 2022).…”
Section: Research Objectivesmentioning
confidence: 99%